Plan de negocio para la creación de un salón de eventos sociales de segunda categoría en la parroquia el Comité del Pueblo, Quito - Ulcuango Colcha, Josselyn Solange (2020)
The present study aims to design a business plan for a second category Social and formal receptions room at the north of Quito, starting with the high quality in the planning and implementation of such events, offering comfortable and friendly facilities, affordable cost and with a special focus on people with difficulty of mobility. Its objective: to determine the appropriate strategic planning for the business, establishing appropriate strategies for marketing to propel it, detailing a functional operating plan and performing a correct financial evaluation to ensure profitability. With appropriate systems of fixing prices, which include percentage of utility and allow enter in the market with competitive values, offering facilities and products of superior quality. The research methods used measure the relevant social characteristics, studying population samples that generate concrete data, among them: quantitative research, with semi-structured surveys, which offer more of a respondent's point of view and present particular details of the object of study. Qualitative research that collects data without numerical measure for understanding the perspective of the participant, deepening in their experiences and perceptions. Opinion Poll method that facilitates the knowledge and analysis of the situation together with the behavior of the interest group; finally, interviews with owners of event rooms and banquets, experts in organizing social events, to obtain relevant information in market research. The results were favorable and show profitability in the project because the revenue will cover costs and expenses; the company plans to recover the initial investment in five years, but to maintain the balance point, it must have a minimum of attendees which cover the price set, in order to avoid losses. As a conclusion, there is an unmet demand in relation to a lounge for events of the proposed features. There is currently no one whose primary strategy is to provide a service with high quality standards, impeccable performance of staff at fair and accessible prices, and then the project is feasible because the financial tools applied determined economic stability. As a recommendation, it is necessary to attract the suitable customer, who has the adequate income and can afford at least two social events a year with a minimum of 150 guests.